Requestioning the Indonesia Government's Public Policy Response to the COVID-19 Pandemic: Black Box Analysis for the Period of January-July 2020 - Dumilah Ayuningtyas; Hayyan Ul Haq; Raden Roro Mega Utami; Sevina Susilia (Frontiers Media S.A., 2021)
Objectives: Indonesia responded the COVID-19 pandemic slowly these last months. The recent reports shown that the rate performance of Indonesian government in handling COVID-19 posits at the 4th worst all over the world. Meanwhile, through responsive, strict, and strategic policy, some Asia countries pushed the elimination case by doing lockdown. This paper questioned how government respond this pandemic, tried to track down the unresponsive and slow decisions, and analyze them comprehensively trough policy system framework. Moreover, we also considered a few feasible and strategic recommendations to accelerate the pandemic responding.Methods: To visualize the anatomy of problems in handling these pandemic responses, this work applied Easton's black box analysis in formulating and introducing public policy. The black box analysis would help us to portray and understood the interests, rationalities, and priorities behind introducing public policies which was implemented to handle this health problem. Besides, the policy triangle framework was used to analyze how environment influenced key actor in making decision.Results: This analysis study discovered the conflict interests in formulating and implementing public policy in handling COVID-19. The public policies are negotiated, discussed, and formulated under black box that ignore transparency, and other good governance principles. Consequently, the substance of public policy represents a certain interest of policy makers, that may conflict with the others and often contradict to the constitutional-based public interests, that is public health. It was impacted the emergence of messy and uncoordinated institutions that implement the conflicted policies. Undeniably, this situation may spark counter-productive ways, attitudes, and actions of people in responding those ambiguous policies. Therefore, this work recommended revising the coherences norms and public policies; reforming the ministry of health in public health's paradigm context; and improving the integration and coordination of cross related institutions, creating a single data on public health, and changing a new paradigm of people, including improving collective awareness in responding and handling COVID-19 appropriately.